CONNECTEDNESS AND COMPACTNESS VIA REGULAR*-OPEN SETS - MISSIER*, S. PIOUS; ANNALAKSHMI, M. (International Journal of Mathematical Archive, 2018)
In this paper, we introduce new concepts, namely regular*-connectedness and regular*-compactness using regular*-open sets. We investigate their basic properties and also discuss their relationships with already existing concepts of connectedness and compactness.